(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
Construction of infrastructure is necessary for the interests of the national economy, because the creation of economic and social development projects in any given country depends on the availability of appropriate infrastructure where its multiple services provide benefits to all projects, thus increasing the possibility of the success of these projects and continue its economic activities. For example, in Industrial Projects where there is aprovision of ports, bridges, roads, means of transportation, gas and oil stations and electricity it will contribute in industrial settlement and thus creating big industrial cities and centers. In addition, the provision of these new means of air, land and Sea transportation contribute in facilitating the exchanging and transfer of goods among cities and countries which resulted in establishing different commercial centers. Not to mention also that the provision of irrigation channels, drainage networks, water treatment plants and desalination contribute to the establishment of agricultural projects. In Iraq, as a result of inefficiency in the management of financial resources as well as non-diversified, financial and administrative corruption, lack of security and political stability of the work of the private sector and foreign investors, we find that the infrastructure were not of the level that achieves productive investments, which serve the development in the Iraqi economy, and therefore other means had to be available contribute to the development of infrastructure, for example (BOT – Build Operate and transfer ) a form of partnership of the public sector with the private sector